Advice Giving, Managing Interruptions and the Construction of 'Teachable Moments'. (7th March 2017) - Slembrouck, Stef; Hall, Christopher
Abstract: The focus of this article is on home visiting in child welfare, an activity which involves a publicly accountable performance of professional tasks in a private space. We specifically examine a recording of a visit by a home learning worker to a mother and her three-year-old child with special needs. In the first part of the article, sequential analysis is combined with an understanding of frame and participant alignment (Goffman). We note how the child's behaviour forces the worker and mother to suspend the advice-giving format. We examine how the interruptions are attended to by the talkers and how twice an interruption is seized upon by the home learning worker to develop a 'teachable moment' in which the mother is coached in the demonstration of a learning sequence. In the second part of the article, we re-examine our analysis together with the practitioner so as to throw light on the context of relevant client and case categories, including the longer-term perspective of this specific professional intervention. This results in an enriched perspective on the interactional 'value' of interruptions.